'The light in all is one' : - Sodhi, Navkirat (Aleph Book Company, 2019)
Guru Nanak was a sixteenth-century reformer and the founder of Sikhism. He was the first of the ten Sikh Gurus. He was born in Talwandi, near Lahore, during a time of political and religious discord and disharmony. Right from an early age, he displayed a deep knowledge of divine subjects and spirituality. He challenged ritualism and shows of piety and attacked the citadels of the caste system. He taught that the core tenets of living a good life were helping those less fortunate, making an honest living and meditating on the name of the Lord so as to overcome human weaknesses